1988
DOI: 10.1143/jjap.27.l53
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Oxides by the Sol-Gel Method Using Alkoxides

Abstract: The superconducting oxide Y-Ba-Cu-O has successfully been fabricated by the sol-gel method using Y, Ba, and Cu alkoxides as starting materials. Powders with specific surface area of 15 m2/g are prepared by this method. An X-ray diffraction pattern attributed to a 1-2-3 structure appears at 750°C and a bulk sample with Tc of 90 K is made by 900°C sintering in an oxygen atmosphere. A film of Tc=80 K with c-axis orientation is also fabricated using the sol-gel paste on an yttrium-stabilized ZrO2 substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…3 ' 4 Therefore, there are some reports of the fabrication of Bi-Sr-Ca-Cu-O film using metal alkoxides, 5 " 7 as well as Y-Ba-Cu-O films. 8 " 14 The authors also reported that Cu alkoxide can be modified to increase its solubility by an OR-substitution reaction of the alkoxide with 2-dimethylaminoethanol in the preparation of In the case of Bi alkoxide, the preparation of a solution of Bi, Sr, Ca, and Cu alkoxides has been reported 5 " 7 but without discussion on the solubility increase of Bi alkoxide in this system. But it is difficult to prepare a homogeneous solution of Bi, Sr, Ca, and Cu alkoxides due to the insolubility of Bi and Cu alkoxides in common organic solvents.…”
Section: Introductionmentioning
confidence: 98%
“…3 ' 4 Therefore, there are some reports of the fabrication of Bi-Sr-Ca-Cu-O film using metal alkoxides, 5 " 7 as well as Y-Ba-Cu-O films. 8 " 14 The authors also reported that Cu alkoxide can be modified to increase its solubility by an OR-substitution reaction of the alkoxide with 2-dimethylaminoethanol in the preparation of In the case of Bi alkoxide, the preparation of a solution of Bi, Sr, Ca, and Cu alkoxides has been reported 5 " 7 but without discussion on the solubility increase of Bi alkoxide in this system. But it is difficult to prepare a homogeneous solution of Bi, Sr, Ca, and Cu alkoxides due to the insolubility of Bi and Cu alkoxides in common organic solvents.…”
Section: Introductionmentioning
confidence: 98%
“…Processing speed is an extremely important economic consideration and hence must be significantly increased if high T, superconductor fibers are to see commercialization. [12] Numerous modified melt-texturing methods, such as the Quench-Melt-Growth, [13,14] the Melt-Powder-Melt-Growth, [15] and the Powder-Melt-Process [16] have been proposed. However, all these techniques have been developed to increase the flux pinning capability of YBa 2 Cu 3 07-, by finely distributing Y 2 BaCuO 5 .…”
Section: -19mentioning
confidence: 99%
“…to become so disordered that the model being used here i.o(a) = 7a e (12) is not useful, so one has a boundary defining the valid-(2a~ Iity limit for this model of Magnetic relaxation measurements have been made on two sets of samples of Y -.Pr_,BaCu 3 0 7 -6 high T, superconductors with 0<x 0. 10.…”
Section: (11)mentioning
confidence: 99%
“…The cutoff, free-space, and guide wave numbers are given by: From these fields, we can calculate the cavity's stored energy, U, the wall loss, P, and the resulting Q: where R s is the surface resistivity in ohms "per square," and the skin depth, 6 skin, is the e-folding distance for the rf wall currents into the imperfect conductor of conductivity 0.…”
Section: A43 Magnetization Measurementsmentioning
confidence: 99%
“…' (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) at which point ps(w) approaches half that of unpinned flux. It increases further for higher frequencies until the flux is effectively completely unpinned; the analytic form of this increase depends on the shape of the pinning potential well.…”
Section: A-5-8mentioning
confidence: 99%